They Said: A Global Perspective on Access to Assistive Technology - Angela K. Boisselle; Lenin C. Grajo (Scholarworks @ WMU, 2018)
International experts in assistive technology from five global regions (South America, Asia Pacific, Europe, Africa, and Australia) and with affiliation to the World Health Organization (WHO) Global Cooperation on Assistive Technology (GATE) community were invited to share their perspectives on the delivery of assistive technology and provision of assistive products in their regions. Four common topics emerged from the experts: (a) user and environmental barriers; (b) policy, funding, and product access; (c) professional training, collaboration, and service delivery; and (d) occupational justice (i.e., empowerment, participation, and progress).